PENGEMBANGAN WEBTOON UNTUK PEMBELAJARAN IPS (EKONOMI) DI SMP - Fauzana Alfiani; Tri Kurniawati; Menik Kurnia Siwi (Universitas Negeri Padang, 2018)
This study aims to develop webtoon as learning media for learning social studies (economics) in junior high school. The methods of this study is a research and development refers to the development model Sugiyono using five stages, namely the potential and problems, information gathering, product design, design validation and design improvements. Data collection techniques in this research and development using the documentation of records and media development activities currently also using for validation expert qutionnaire.Based on the results of validation by experts, the obtained value of the average score on the media 4.7with the category of Very Good for the placement and selection of colors in the image on the media is appropriate, presentation of the material is appropriate, developed learning media is easy to use by the user. In the material obtained an average score of 3.7 with the category of Good because of the depth of material on the media is enough, the presentation of the material has been understood and it is systematic, the range of material is in conformity with the purpose of learning. On language obtained an average score of 3.57 with the category of Good because of the language used in the media can be understood, writing in the material is appropriate terms, sentences medium used in a simple and straight forward, the language used in accordance with the emotional maturity of learners. In order to obtain the overall average is 4.02 with the category of Good and can be said to be